The Long‐Term Journey of a Tuberculosis Patient With Triple Organ Involvement and Rheumatological Disease: A Case Study and Literature Review - Homina Saffar; Pooria Sobhanian; Shahriar Alian; David Darvishnia; Mansoureh Baradaran (Clinical Case Reports)
ABSTRACT Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis bacteria, which is more prevalent among immunocompromised individuals. According to the distribution of affected organs, this infection can be categorized as either pulmonary or extrapulmonary TB. Immunodeficiency states resulting from rheumatological disorders and the use of immunosuppressive medications, such as in Behçet's disease (BD), are potential predisposing factors for TB, particularly in cases involving multiple organs. These situations can introduce challenges in both the diagnosis and treatment of patients. We describe a 43‐year‐old man with a history of BD who presented with symptoms of weight loss, abdominal pain, and shortness of breath. His chest X‐ray revealed cavities and calcifications, while an abdominal X‐ray demonstrated signs of intestinal obstruction and adhesions. Subsequent TB diagnosis led to a 6‐month course of a TB treatment regimen. Despite treatment initiation, the patient developed a brain abscess 1 year later, necessitating surgical intervention. Following the procedure, he received another 1‐year course of a TB treatment regimen and experienced full recovery without any complications during a 2‐year follow‐up period. Notably, the patient recently received a Sinopharm COVID‐19 vaccine and subsequently developed seizures that are currently being managed with anticonvulsant therapy. This case report emphasizes the significance of including pulmonary TB in complex medical cases, especially in individuals with autoimmune diseases. Early diagnosis and treatment are crucial for improving outcomes and reducing the risk of complications. Furthermore, it highlights the possible correlation between TB and BD, along with the potential adverse reactions to COVID‐19 vaccines in this population, which necessitate special consideration by healthcare professionals.